Analisis Kegagalan Pada Komponen Poros Pompa Industri - Restyarno Agung Nugroho; Priyo Tri Iswanto (Proceedings Series on Physical & Formal Sciences, 2021)
Pumps are very important industrial equipment in the petroleum industry. The component that often fails is the pump shaft. Therefore, it is necessary to conduct a failure analysis of this component to determine the mode/type of failure and how it occurred. This study used Scanning Electron Microscope (SEM), metallographic test, chemical composition test, and Brinell hardness test with the standard UNSS42000 material. Fatigue test to determine the fatigue limit of the shaft with a rotary bending fatigue test. The failure model that occurred was fatigue failure characterized by initial cracks, crack growth, ratchet marks, sudden fracture areas. Based on the comparison between the test results of chemical composition and mechanical properties of the material, the drive shaft pump material was suitable for the UNS S42000 material.